2020
DOI: 10.1111/1471-0528.16553
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s use of e‐cigarettes in the UK: a cross‐sectional survey

Abstract: To estimate prevalence of vaping in pregnancy. Compare characteristics and attitudes between exclusive smokers and vapers, and between exclusive vapers and dual users (smoke and vape). Design Cross-sectional survey Setting Hospitals across England and Scotland Population Pregnant women attending antenatal clinics in 2017 Methods Women 8-24 weeks gestation completed screening questions about their smoking and vaping. Current or recent ex-smokers and/or vapers completed a full detailed survey about vaping and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
(104 reference statements)
2
32
0
Order By: Relevance
“…It is possible that some of the decline in prescribing of NRT is related to increased use of electronic cigarettes; the number of e-cigarette users in the general population in Great Britain increased from 0.7 million in 2012 to 2.9 million in 2017. 14 However, in the UK, use of e-cigarettes by pregnant women is not particularly widespread; a 2017 survey found that only 5% of pregnant women reported any vaping during pregnancy and only around 1% reported exclusive vaping (ie, they had stopped smoking). 14 It seems unlikely, therefore, that vaping behavior would have had a substantial impact on pregnant women’s propensity to use NRT and hence, on primary care prescribing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that some of the decline in prescribing of NRT is related to increased use of electronic cigarettes; the number of e-cigarette users in the general population in Great Britain increased from 0.7 million in 2012 to 2.9 million in 2017. 14 However, in the UK, use of e-cigarettes by pregnant women is not particularly widespread; a 2017 survey found that only 5% of pregnant women reported any vaping during pregnancy and only around 1% reported exclusive vaping (ie, they had stopped smoking). 14 It seems unlikely, therefore, that vaping behavior would have had a substantial impact on pregnant women’s propensity to use NRT and hence, on primary care prescribing.…”
Section: Discussionmentioning
confidence: 99%
“… 14 However, in the UK, use of e-cigarettes by pregnant women is not particularly widespread; a 2017 survey found that only 5% of pregnant women reported any vaping during pregnancy and only around 1% reported exclusive vaping (ie, they had stopped smoking). 14 It seems unlikely, therefore, that vaping behavior would have had a substantial impact on pregnant women’s propensity to use NRT and hence, on primary care prescribing. Nevertheless, research investigating any relationships between smoking, e-cigarette, and NRT use by pregnant women, including impacts of longitudinal changes in prevalence of use and potential trade-offs between e-cigarette use and primary care NRT prescribing, would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of vaping estimated in this study was lower than that from a survey of women who were attending hospital antenatal care appointments at 8 to 24 weeks into their pregnancy, which was conducted in England and Scotland between June and November 2017 [ 37 ]. Like our study, the antenatal survey found that most of the women who vaped also smoked, however they reported a higher prevalence of current vaping than we observed: 4.8% (95%CI 4.1 to 5.6), of which 1.3% (95%CI 1.0 to 1.8) were exclusive vapers and 3.5% (95%CI 2.9 to 4.2) were dual cigarette smokers and vapers.…”
Section: Discussionmentioning
confidence: 75%
“…Use of electronic cigarettes (EC/vaping) is a potential smoking cessation intervention in pregnancy; there is some evidence for effectiveness in non-pregnant smokers [ 10 , 11 ], and they are increasingly used in pregnancy [ 12 , 13 ], including for cessation [ 14 , 15 ]. In the UK around 5% of pregnant women report vaping [ 16 ]. Pregnant women and health professionals (HPs) consider vaping safer than smoking [ 17 , 18 , 19 , 20 ], yet also have concerns about safety [ 14 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%